Gender dysphoria presenting as genital self-mutilation: A case report - Arun, Arun kumar; Singh, Santosh Kumar; Saha, Atreyee; Kumar, Vivek; Dwivedi, Chandrark (Indian Journal of Case Reports, 2026)
Genital self-mutilation is a rare but critical clinical event that commonly reflects severe psychological distress, often linked to psychiatric illness or unresolved gender identity conflict. We describe a 20-year-old biological male who presented after intentionally amputating his penis and testes as part of an unsupervised attempt at self-directed gender transition. The procedure was carried out at home under self-administered local anesthesia, and the patient arrived hemodynamically stable, enabling immediate surgical wound care and stabilization. Subsequent psychiatric assessment confirmed a diagnosis of gender dysphoria with coexisting major depressive disorder, neither of which had been previously treated. This case illustrates the degree of distress that may accompany persistent, unsupported gender incongruence and emphasizes the need for timely mental-health intervention, structured gender-affirming care pathways, and coordinated multidisciplinary management. Improving awareness, reducing stigma, and ensuring accessible medical and psychological support for individuals with gender dysphoria are crucial measures to prevent irreversible self-harm and improve long-term outcomes.